Magnetic properties and retained austenite quantification in SAE 4340 steel - Ajus,C. (2009)
Magnetic properties (coercive force and saturation magnetization) of SAE 4340 steel, heat treated in different ways, were measured in a Vibrating Sample Magnetometer. Four soaking temperatures were investigated: 860°C, 960°C, 1060°C and 1160°C. The oil-quenched samples were tempered at different temperatures between the range of 200°C and 650°C. The increase of the soaking temperature promotes the decrease of the saturation magnetization, which is mainly due to the retained austenite in the steel. This austenite transforms into bainite during tempering between 200°C and 300°C. The saturation magnetization measurements were used to quantify the amount of retained austenite in the different samples. The coercive force of the steel varied from 115.0 Oe (9151.7 A/m) to 133.0 Oe (10584.1 A/m), depending on the heat treatment condition.